2007
DOI: 10.1097/brs.0b013e31815ce6c4
|View full text |Cite
|
Sign up to set email alerts
|

Dorsally Sequestered Cervical Disc Herniation

Abstract: It is important to appropriately differentiate dorsally sequestered disc herniation from other epidural mass lesions such as extradural tumor before operation and essential to perform early and sufficient surgical decompression of the spinal cord to prevent poor postoperative course in cases of acute onset and rapid progression of the paralysis caused by disc herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…4,25,28,29,31,36,43 Magnetic resonance imaging appears to be the method of choice for diagnosis. Generally, a posterior disc fragment demonstrated a heterogeneous low to isointense signal on T1-weighted imaging.…”
Section: Discussionmentioning
confidence: 99%
“…4,25,28,29,31,36,43 Magnetic resonance imaging appears to be the method of choice for diagnosis. Generally, a posterior disc fragment demonstrated a heterogeneous low to isointense signal on T1-weighted imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Originally in three more patients unusual sequestrated disc fragments were mistaken for another space occupying lesion and were operated. The biopsy revealed that they were disc material, thus accounting for total 10 cases reported in the entire literature by different authors [7,9,13]. The above data clearly indicate the extreme rarity of such non-traumatic extruded extradural disc in the cervical spine.…”
Section: Discussionmentioning
confidence: 74%
“…Few reports have suggested excision of the disc through posterior approach via laminectomy [6-9], while others opine that it can be excised by performing corpectomy [1] or microdiscectomy through adjacent disc space via anterior approach [10]. This varied opinion led us to retrospectively analyze our 396 cervical disc prolapse cases that we had treated over a period of 7 years.…”
Section: Introductionmentioning
confidence: 99%
“…Quoted as PEMLIFan acronym for posterior epidural migration of lumbar intervertebral disc fragment, it is a very rare phenomenon with less than fifty cases reported in the literature. Migration of the sequestrated segment is not only limited to the lumbar region, but has also been reported in the thoracic (2) as well as the cervical (3,4) segments. However, this is most commonly seen in the lumbar spinal segments and least in the cervical region.…”
Section: Introductionmentioning
confidence: 99%